2021
DOI: 10.1155/2021/5515654
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Composition of Lentils: Physiological Functions, Antinutritional Effects, and Bioavailability Enhancement

Abstract: Lentil (Lens culinaris) is an important nutritious crop, grown and consumed throughout the world due to its high macro- and micronutrients contents, including minerals. Minerals have several beneficial influences on human health. Thus, lentils play a major role in food security, particularly among low-income countries. The current review aims to highlight the present knowledge on the mineral composition of lentils, compare it with the recommended dietary allowance and adequate intake of minerals, investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Like many other legumes, lentils ( Lens culinaris L.) from the Leguminosae family, cultivated by communities all over the world for centuries, are small edible legumes (Benayad & Aboussaleh, 2021; Samaranayaka, 2017). In general, lentils, one of the most widely grown and marketed dried legumes worldwide, are a good source of protein, carbohydrates, and fiber, but low in fat (Campos‐Vega et al., 2010; Yu‐Wei & Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Like many other legumes, lentils ( Lens culinaris L.) from the Leguminosae family, cultivated by communities all over the world for centuries, are small edible legumes (Benayad & Aboussaleh, 2021; Samaranayaka, 2017). In general, lentils, one of the most widely grown and marketed dried legumes worldwide, are a good source of protein, carbohydrates, and fiber, but low in fat (Campos‐Vega et al., 2010; Yu‐Wei & Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As for the other elements, several inorganic elements were present; the K was the most abundant with percentages of 0.78, 0.69, and 1.20% in Lf1, Lf2, and LF3 samples respectively, excepting the sample LF4, where the Ca was the mineral the most dominant (0.25%), followed by P as the second predominant inorganic element. Hefnawy 11 , Zia-Ul-Haq et al 1 and Benayad & Aboussaleh 14 obtained identical results where the K and P were the major elements in the lentil. The addition of lentil flour in yogurt had elevated the rate of Ca from 0.16 to 0.21% and from 0.11 to 0.25%; and that of Na from 0.07 to 0.13% and from 0.04 to 0.13% for the raw and roasted lentil flour, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…A five-day nitrogen balance experiment in man additionally showed that methionine was the first restricting amino acid in quite a while for man. [10][11][12][13][14][15][16][17]…”
Section: Protein Fractions In Lentilmentioning
confidence: 99%